2019
DOI: 10.1002/er.4803
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation and comparison of multistage indirect evaporative cooling systems in two operation modes

Abstract: The evaporative cooling technique is an efficient approach for cooling application. This study aims to establish a performance evaluation method to advance the appropriate design for multistage indirect evaporative cooling systems. A mathematical formulation has been developed for the indirect evaporative cooler (IEC). After the validation, the mathematical model was used to analyze the evaluation criteria by considering the simultaneous influence of the cooling effectiveness, the pressure drop, and the coolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…To improve the simple IEC, Maisotsenko proposed a new flow arrangement for IEC, termed as Maisotsenko-cycle (M-cycle) IEC. This concept made a great contribution to the IEC development [33][34][35]. M-cycle IEC theoretically could decrease the minimum temperature from DEC's wet-bulb temperature down to the dew temperature of the intake air while avoiding the addition of moisture into the supply air [36][37][38].…”
Section: Indirect Evaporative Cooling (Iec)mentioning
confidence: 99%
“…To improve the simple IEC, Maisotsenko proposed a new flow arrangement for IEC, termed as Maisotsenko-cycle (M-cycle) IEC. This concept made a great contribution to the IEC development [33][34][35]. M-cycle IEC theoretically could decrease the minimum temperature from DEC's wet-bulb temperature down to the dew temperature of the intake air while avoiding the addition of moisture into the supply air [36][37][38].…”
Section: Indirect Evaporative Cooling (Iec)mentioning
confidence: 99%
“…The indirect evaporation cooler was already given a mathematical basis (IEC). Following validation, the mathematical model had been utilized to examine the assessment criteria while simultaneously considering the effects of the cooling capacity, pressure drop, and multi-stages IEC functioning in two modes [10]. The Mode-2 IEC has a regenerative M-cycle system, whereas the Mode-1 IEC is a typical counter flow device.…”
Section: Introductionmentioning
confidence: 99%
“…Pakari et al 13 compared one-dimensional and three-dimensional models of REC with the experimental result and concluded that the one-dimensional model is adequate enough to predict the performance. Cui et al 14 simulated multistage evaporative cooler and found some trade-off between performance and fan power. Wang et al 15 conducted a combined energy–exergy analysis of IEC and optimized for thermal performance.…”
Section: Introductionmentioning
confidence: 99%